Bystander Intervention in Intimate Partner Violence: An Audio Vignette Study of Heterosexual, Gay, and Lesbian Dating Partners. Issue 3 (February 2023) - Graham, Kristen; LaChance, Abby; Wormwood, Jolie B.
Intimate partner violence (IPV) is a prolific and growing issue that can have long-lasting negative consequences for the health and safety of those involved. Bystander intervention is one method for helping to combat incidents of IPV, as research suggests that bystanders are frequently present at the scene of assaults and incidents of IPV. This study explored individual differences of bystanders that may influence whether they decide to intervene in an unfolding incident of IPV, as well as how the likelihood of intervening may vary as a function of the apparent gender or sexual orientation of the individuals involved in an incident of IPV. Participants were recruited from an online survey platform to obtain a balanced sample of heterosexual and sexual minority individuals. Participants completed a bystander task where they listened to an audio vignette of an unfolding IPV incident and were instructed to stop the audio if/when they would intervene in a real-life context. Participants were randomly assigned to listen to one of four versions of the vignette in which the apparent gender of the aggressor and victim were manipulated. Results revealed participants were more likely to intervene if they identified as a sexual minority (vs. as a heterosexual), reported less rape myth acceptance, or had greater endorsement of gender equality. Results also revealed that associations between bystander characteristics and intervening behavior largely did not differ across vignette conditions, suggesting that they may influence the likelihood of intervening consistently across incidents of IPV regardless of the apparent gender and sexual orientation of the aggressor and victim. However, participants in general were most likely to intervene in the male aggressor/female victim vignette. Implications for IPV prevention programming—including the need to include more diverse and less heteronormative depictions of IPV—are discussed.